A high-strength polytetrafluoroethylene cable film and preparation method thereof

By using materials such as alumina nanofibers and UiO MOFs in PTFE cable films, combined with electrospinning and hot pressing processes, the problem of insufficient mechanical properties of traditional PTFE films is solved, and high strength, flexibility and electrical insulation are achieved. Improve and simplify the preparation process.

CN118895031BActive Publication Date: 2024-12-13TIANJIN BOHAI WANYE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411399387.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-13
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Traditional PTFE cable films have limitations in terms of mechanical strength and flexibility, and the processing technology is complex and costly, making it difficult to meet the needs of high-demand applications. At the same time, doped fillers are prone to introduce electrical conductivity or dispersion, making it difficult to maintain electrical insulation performance.

Method used

Using a combination of alumina nanofibers, UiO type MOFs, silane coupling agents and antioxidants and PTFE matrix, high-strength PTFE cable films are prepared through electrospinning and hot pressing processes to form a uniform reinforcement network to enhance Mechanical properties and structural stability.

Benefits of technology

The mechanical strength, wear resistance and thermal stability of the PTFE cable film is significantly improved while maintaining electrical insulation properties, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895031B_ABST
    Figure CN118895031B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of cable films, and specifically provides a high-strength polytetrafluoroethylene cable film and a preparation method thereof, wherein the polytetrafluoroethylene cable film comprises the following raw materials in parts by weight: 70-90 parts of polytetrafluoroethylene, 10-20 parts of alumina nanofibers, 7-10 parts of UiO type MOFs, 2-4 parts of silane coupling agents, 3-5 parts of antioxidants, and 1-2 parts of triphenyl phosphate. The present invention introduces alumina nanofibers and UiO type MOFs materials into a polytetrafluoroethylene matrix, and closely combines them with polytetrafluoroethylene, thereby significantly improving the strength and flexibility of the cable film, while not affecting its insulation performance, and can meet higher application requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable films, and in particular to a high-strength polytetrafluoroethylene cable film and a preparation method thereof. Background Art

[0002] Polytetrafluoroethylene (PTFE) is an excellent high-performance polymer. It is widely used in the field of cable films due to its excellent chemical resistance, high temperature stability and low friction coefficient. However, traditional PTFE cable films have certain limitations in mechanical strength and flexibility, which restricts its use in certain high-demand applications. In particular, in situations where high strength and wear resistance are required, pure PTFE materials are often difficult to meet actual needs. In addition, the processing technology of PTFE film is complicated and the cost is high, which limits its application range to a certain extent. Therefore, improving the mechanical properties of PTFE cable film while maintaining its excellent electrical insulation and chemical stability has become the focus of current research.

[0003] Existing technologies attempt to enhance the performance of PTFE cable films by doping with different types of fillers, but these improvement schemes often have some problems. For example, commonly used inorganic fillers such as carbon nanotubes, graphene, etc., although they can improve mechanical strength and thermal conductivity to a certain extent, often introduce electrical conductivity, resulting in a decrease in the electrical insulation performance of the material. While organic fillers contribute to improving flexibility and impact resistance, their heat resistance and chemical corrosion resistance are generally not as good as inorganic fillers. In addition, these fillers have poor dispersibility in the PTFE matrix, which easily causes the agglomeration of the material, resulting in uneven overall performance and difficulty in achieving the desired enhancement effect. Therefore, it is of great practical significance to develop a PTFE cable film that can significantly improve mechanical strength and flexibility while maintaining electrical insulation performance. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-strength polytetrafluoroethylene cable film and a preparation method thereof.

[0005] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: the present invention proposes a high-strength polytetrafluoroethylene cable film, and the polytetrafluoroethylene cable film comprises the following raw materials in parts by weight: 70-90 parts of polytetrafluoroethylene, 10-20 parts of alumina nanofibers, 7-10 parts of UiO type MOFs, 2-4 parts of silane coupling agent, 3-5 parts of antioxidant, and 1-2 parts of triphenyl phosphate.

[0006] Preferably, the method for preparing the alumina nanofibers comprises the following steps:

[0007] A1. Dissolve aluminum salt in water, add aluminum powder, mix well, and react at 60-80℃ for 6-12 hours to obtain aluminum sol solution;

[0008] A2, adding polyvinyl alcohol and polyvinyl pyrrolidone to the aluminum sol solution prepared in step A1, stirring evenly until the solution becomes a transparent and viscous mixture, injecting it into the syringe of the electrospinning device, adjusting the voltage of the electrospinning device to 10-30 kV, setting the distance between the nozzle and the collecting plate to 10-20 cm, starting the electrospinning device, stretching the mixture into nanofibers through the action of the electrostatic field, collecting it on the collecting plate, and forming a fiber film;

[0009] A3. Dry the fiber membrane obtained in step A2 at room temperature for 24 h, then put it into a high-temperature furnace, heat it to 600-800°C, sinter it for 2-4 h, and then cool it to room temperature to obtain alumina nanofibers.

[0010] Preferably, in step A1, the aluminum salt is any one of aluminum chloride and aluminum nitrate, and the mass ratio of the aluminum salt to water is 20-30:100; the mass ratio of the aluminum powder to the aluminum salt is 1:1.

[0011] Preferably, in step A2, the mass ratio of polyvinyl alcohol to polyvinyl pyrrolidone is 1:1, and the mass ratio of polyvinyl alcohol to aluminum salt is 1:1.

[0012] Preferably, the method for preparing the UiO type MOFs comprises the following steps:

[0013] ①. Add metal salt, organic ligand and regulator into DMF and dissolve evenly to form a precursor solution;

[0014] ②. The precursor solution prepared in step ① was placed in a reactor lined with polytetrafluoroethylene, and heated in an oven at 120 °C for 12-24 h. After cooling to room temperature, the supernatant was removed by centrifugation at 6000-8000 rpm. The precipitate was washed alternately with ethanol and deionized water three times, and dried in a vacuum drying oven at 60 °C for 24 h to obtain UiO-type MOFs.

[0015] Preferably, in step ①, the metal salt is any one of zirconium chloride and zirconium oxychloride, the organic ligand is any one of terephthalic acid, biphenyl-4-4'-dicarboxylic acid and trimesic acid, and the regulator is any one of formic acid, acetic acid and benzoic acid.

[0016] Preferably, in step ①, the usage ratio of metal salt, organic ligand, regulator and DMF is 1 mol: 1 mol: 3~5 mol: 2~4 L.

[0017] Preferably, the silane coupling agent comprises the following raw materials in parts by weight: 1-2 parts of 3-aminopropyltriethoxysilane, 4-6 parts of γ-aminopropyltrimethoxysilane, and 3-5 parts of 3-methacryloxypropyltrimethoxysilane.

[0018] Preferably, the antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0019] The present invention also provides a method for preparing a high-strength polytetrafluoroethylene cable film, which specifically comprises the following steps:

[0020] S1. Add polytetrafluoroethylene, alumina nanofibers, UiO-type MOFs, silane coupling agent, antioxidant, and triphenyl phosphate into a mixer according to weight parts, mix well, and obtain a mixed material;

[0021] S2, placing the mixed material prepared in step S1 into a mold, and preparing a formed film by hot pressing using a hot press, the hot pressing temperature is 250-300° C., the pressure is 10-20 MPa, and the pressing time is 30-60 min;

[0022] S3, performing surface grinding processing on the film formed in step S2 to obtain a high-strength polytetrafluoroethylene cable film.

[0023] The beneficial effects achieved by the present invention are as follows:

[0024] The present invention significantly improves the mechanical properties and thermal stability of PTFE cable film by adding alumina nanofibers, UiO type MOFs and a specific proportion of silane coupling agent, antioxidant and triphenyl phosphate into a polytetrafluoroethylene (PTFE) matrix. Alumina nanofibers, as an inorganic filler, can improve the tensile strength and wear resistance of PTFE film without significantly increasing the material density. And it has good dispersibility, forming a uniform reinforcement network in the PTFE matrix, further improving the structural stability of the film; in addition, the high insulation of alumina nanofibers ensures the advantage of the film in maintaining electrical insulation performance, and the insulation effect of the cable film will not be reduced due to the introduction of fillers. After the alumina nanofibers and UiO type MOFs materials are mixed and hot pressed, they are closely combined with polytetrafluoroethylene. Under the action of external stress, the alumina nanofibers can effectively disperse and transfer stress to prevent the formation and expansion of cracks. The presence of MOFs increases the structural complexity of the film, and its porous network structure can absorb and disperse stress, thereby reducing stress concentration and significantly improving the tensile properties of the film. The introduction of alumina nanofibers into the PTFE matrix makes the microstructure of the material more compact and uniform, and the porous structure of MOFs further optimizes the internal porosity and distribution of the film, avoiding the common voids and weak interface areas in traditional PTFE films. At the same time, the present invention effectively simplifies the preparation process, reduces the overall processing cost, and improves the market competitiveness of the product through improved formula and process design. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] FIG1 is a scanning electron microscope image of the aluminum oxide nanofibers prepared in Example 1;

[0027] FIG. 2 is a scanning electron microscope image of the UiO type MOFs prepared in Example 1. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0029] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0030] Example 1: This example proposes a high-strength polytetrafluoroethylene cable film, which includes the following raw materials in parts by weight: 80 parts of polytetrafluoroethylene, 15 parts of alumina nanofibers, 7 parts of UiO-type MOFs, 2 parts of silane coupling agent, 3 parts of 2,6-di-tert-butyl-4-methylphenol, and 2 parts of triphenyl phosphate.

[0031] The method for preparing the aluminum oxide nanofibers comprises the following steps:

[0032] A1. Dissolve 20 g of aluminum salt in 100 mL of water, add 20 g of aluminum powder, mix well, and react at 80 °C for 6 h to obtain an aluminum sol solution;

[0033] A2, adding 20 g of polyvinyl alcohol and 20 g of polyvinyl pyrrolidone to the aluminum sol solution prepared in step A1, stirring evenly until the solution becomes a transparent and viscous mixture, injecting it into the syringe of the electrospinning device, adjusting the voltage of the electrospinning device to 20 kV, setting the distance between the nozzle and the collecting plate to 20 cm, starting the electrospinning device, stretching the mixture into nanofibers through the action of the electrostatic field, collecting it on the collecting plate, and forming a fiber film;

[0034] A3. Dry the fiber membrane obtained in step A2 at room temperature for 24 h, then put it into a high-temperature furnace, heat it to 700°C, sinter it for 3 h, and then cool it to room temperature to obtain alumina nanofibers.

[0035] The preparation method of the UiO type MOFs comprises the following steps:

[0036] ①, add 10 mmol zirconium chloride, 10 mmol terephthalic acid, and 30 mmol formic acid into 20 mL DMF and dissolve evenly to form a precursor solution;

[0037] ②. The precursor solution prepared in step ① was placed in a reactor lined with polytetrafluoroethylene, heated in an oven at 120 °C for 24 h, cooled to room temperature, centrifuged at 6000 rpm to remove the supernatant, and the precipitate was washed alternately with ethanol and deionized water three times, and dried in a vacuum drying oven at 60 °C for 24 h to obtain UiO type MOFs.

[0038] The silane coupling agent comprises the following raw materials in parts by weight: 1 part of 3-aminopropyltriethoxysilane, 6 parts of γ-aminopropyltrimethoxysilane, and 3 parts of 3-methacryloxypropyltrimethoxysilane.

[0039] This embodiment also provides a method for preparing a high-strength polytetrafluoroethylene cable film, which specifically includes the following steps:

[0040] S1. Add polytetrafluoroethylene, alumina nanofibers, UiO-type MOFs, silane coupling agent, antioxidant, and triphenyl phosphate into a mixer according to weight parts, mix well, and obtain a mixed material;

[0041] S2, placing the mixed material prepared in step S1 into a mold, and preparing a formed film by hot pressing using a hot press, the hot pressing temperature is 250° C., the pressure is 20 MPa, and the pressing time is 40 min;

[0042] S3, performing surface grinding processing on the film formed in step S2 to obtain a high-strength polytetrafluoroethylene cable film.

[0043] Example 2: This example proposes a high-strength polytetrafluoroethylene cable film, which includes the following raw materials in parts by weight: 70 parts of polytetrafluoroethylene, 10 parts of alumina nanofibers, 8 parts of UiO-type MOFs, 4 parts of silane coupling agent, 5 parts of 2,6-di-tert-butyl-4-methylphenol, and 1 part of triphenyl phosphate.

[0044] The method for preparing the aluminum oxide nanofibers comprises the following steps:

[0045] A1. Dissolve 25 g of aluminum salt in 100 mL of water, add 25 g of aluminum powder, mix well, and react at 60°C for 12 h to obtain an aluminum sol solution;

[0046] A2, adding 25 g of polyvinyl alcohol and 25 g of polyvinyl pyrrolidone to the aluminum sol solution prepared in step A1, stirring evenly until the solution becomes a transparent and viscous mixture, injecting it into the syringe of the electrospinning device, adjusting the voltage of the electrospinning device to 10 kV, setting the distance between the nozzle and the collecting plate to 10 cm, starting the electrospinning device, stretching the mixture into nanofibers through the action of the electrostatic field, collecting it on the collecting plate, and forming a fiber film;

[0047] A3. Dry the fiber membrane obtained in step A2 at room temperature for 24 h, then put it into a high-temperature furnace, heat it to 600° C., sinter it for 4 h, and then cool it to room temperature to obtain alumina nanofibers.

[0048] The preparation method of the UiO type MOFs comprises the following steps:

[0049] ①. Add 10 mmol zirconium oxychloride, 10 mmol biphenyl-4-4'-dicarboxylic acid, and 50 mmol benzoic acid into 40 mL DMF and dissolve evenly to form a precursor solution.

[0050] ②. The precursor solution prepared in step ① was placed in a reactor lined with polytetrafluoroethylene, heated in an oven at 120 °C for 20 h, cooled to room temperature, centrifuged at 8000 rpm to remove the supernatant, and the obtained precipitate was washed alternately with ethanol and deionized water three times, and dried in a vacuum drying oven at 60 °C for 24 h to obtain UiO-type MOFs.

[0051] The silane coupling agent comprises the following raw materials in parts by weight: 2 parts of 3-aminopropyltriethoxysilane, 4 parts of γ-aminopropyltrimethoxysilane, and 4 parts of 3-methacryloxypropyltrimethoxysilane.

[0052] This embodiment also provides a method for preparing a high-strength polytetrafluoroethylene cable film, which specifically includes the following steps:

[0053] S1. Add polytetrafluoroethylene, alumina nanofibers, UiO-type MOFs, silane coupling agent, antioxidant, and triphenyl phosphate into a mixer according to weight parts, mix well, and obtain a mixed material;

[0054] S2, placing the mixed material prepared in step S1 into a mold, and preparing a formed film by hot pressing using a hot press, the hot pressing temperature is 300° C., the pressure is 15 MPa, and the pressing time is 30 min;

[0055] S3, performing surface grinding processing on the film formed in step S2 to obtain a high-strength polytetrafluoroethylene cable film.

[0056] Example 3: This example proposes a high-strength polytetrafluoroethylene cable film, which includes the following raw materials in parts by weight: 90 parts of polytetrafluoroethylene, 20 parts of alumina nanofibers, 10 parts of UiO-type MOFs, 3 parts of silane coupling agent, 4 parts of 2,6-di-tert-butyl-4-methylphenol, and 1 part of triphenyl phosphate.

[0057] The method for preparing the aluminum oxide nanofibers comprises the following steps:

[0058] A1. Dissolve 30 g of aluminum salt in 100 mL of water, add 30 g of aluminum powder, mix well, and react at 70 °C for 8 h to obtain an aluminum sol solution;

[0059] A2, adding 30 g of polyvinyl alcohol and 30 g of polyvinyl pyrrolidone to the aluminum sol solution prepared in step A1, stirring evenly until the solution becomes a transparent and viscous mixture, injecting it into the syringe of the electrospinning device, adjusting the voltage of the electrospinning device to 15 kV, setting the distance between the nozzle and the collecting plate to 15 cm, starting the electrospinning device, stretching the mixture into nanofibers through the action of the electrostatic field, collecting it on the collecting plate, and forming a fiber film;

[0060] A3. Dry the fiber membrane obtained in step A2 at room temperature for 24 h, then put it into a high-temperature furnace, heat it to 800° C., sinter it for 2 h, and then cool it to room temperature to obtain alumina nanofibers.

[0061] The preparation method of the UiO type MOFs comprises the following steps:

[0062] ①. Add 10 mmol zirconium chloride, 10 mmol trimesic acid, and 40 mmol acetic acid into 30 mL DMF and dissolve evenly to form a precursor solution;

[0063] ②. The precursor solution prepared in step ① was placed in a reactor lined with polytetrafluoroethylene, heated in an oven at 120 °C for 12 h, cooled to room temperature, centrifuged at 7000 rpm to remove the supernatant, and the obtained precipitate was washed alternately with ethanol and deionized water three times, and dried in a vacuum drying oven at 60 °C for 24 h to obtain UiO type MOFs.

[0064] The silane coupling agent comprises the following raw materials in parts by weight: 2 parts of 3-aminopropyltriethoxysilane, 5 parts of γ-aminopropyltrimethoxysilane, and 5 parts of 3-methacryloxypropyltrimethoxysilane.

[0065] This embodiment also provides a method for preparing a high-strength polytetrafluoroethylene cable film, which specifically includes the following steps:

[0066] S1. Add polytetrafluoroethylene, alumina nanofibers, UiO-type MOFs, silane coupling agent, antioxidant, and triphenyl phosphate into a mixer according to weight parts, mix well, and obtain a mixed material;

[0067] S2, placing the mixed material prepared in step S1 into a mold, and preparing a formed film by hot pressing using a hot press, the hot pressing temperature is 280° C., the pressure is 20 MPa, and the pressing time is 60 min;

[0068] S3, performing surface grinding processing on the film formed in step S2 to obtain a high-strength polytetrafluoroethylene cable film.

[0069] Comparative Example 1: This comparative example proposes a method for preparing a high-strength polytetrafluoroethylene cable film, which differs from Example 1 only in that no aluminum oxide nanofibers are added, and the remaining components, component contents, and experimental steps are the same as those in Example 1.

[0070] Comparative Example 2: This comparative example proposes a method for preparing a high-strength polytetrafluoroethylene cable film, which differs from Example 1 only in that UiO-type MOFs are not added, and the remaining components, component contents, and experimental steps are the same as those in Example 1.

[0071] Experimental Example 1: The microstructures of the alumina nanofibers and UiO-type MOFs prepared in Example 1 were observed using a scanning electron microscope.

[0072] Figure 1 is a scanning electron microscope image of the aluminum oxide nanofibers prepared in Example 1. As shown in the figure, the aluminum oxide nanofibers prepared using bagasse are relatively uniform. Figure 2 is a scanning electron microscope image of the UiO type MOFs prepared in Example 1. As shown in the figure, the prepared MOFs material has a particle size of about 100 nm and is uniform in size.

[0073] Experimental Example 2: Performance Test:

[0074] Tensile property test: Under the conditions of an ambient temperature of 23° C. and a relative humidity of 50%, the tensile strength and elongation at break of the polytetrafluoroethylene cable films prepared in Examples 1-3 and Comparative Examples 1-2 were tested on an electronic universal testing machine at a tensile speed of 10 mm / min;

[0075] Hydrolysis percentage test: The polytetrafluoroethylene cable films prepared in Examples 1-3 and Comparative Examples 1-2 were placed in a vacuum oven at 100°C for 12 h, weighed and recorded as W0, and then immersed in deionized water at 80°C for 72 h. The films were taken out and placed in a vacuum oven at 100°C for 12 h, weighed and recorded as W0. t , the hydrolysis percentage of the membrane = [(W0-W t ) / W0]×100%;

[0076] Electrical insulation performance test: Using a high voltage insulation resistance tester, under the condition of a test voltage of 500V DC, the insulation resistance values ​​of the polytetrafluoroethylene cable films prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The test results are shown in Table 1.

[0077] Table 1 Performance test data

[0078]

[0079] As shown in Table 1, the polytetrafluoroethylene cable films prepared in Examples 1-3 are superior to those in Comparative Examples 1-2 in terms of tensile strength, elongation at break and hydrolysis stability, showing excellent chemical stability and mechanical properties. At the same time, the polytetrafluoroethylene cable films prepared in Examples 1-3 and Comparative Examples 1-2 maintain good electrical insulation properties. Analysis shows that after the added alumina nanofibers and UiO-type MOFs are uniformly distributed in the polytetrafluoroethylene cable film, the strength, flexibility and stability of the cable film can be effectively improved without reducing its resistance performance.

[0080] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design methods and embodiments similar to the technical solution without creativity, which should all fall within the protection scope of the present invention.

Claims

1. A high-strength polytetrafluoroethylene cable film, characterized in that: The polytetrafluoroethylene cable film comprises the following raw materials in parts by weight: 70-90 parts of polytetrafluoroethylene, 10-20 parts of alumina nanofibers, 7-10 parts of UiO type MOFs, 2-4 parts of silane coupling agent, 3-5 parts of antioxidant, and 1-2 parts of triphenyl phosphate; The preparation method of the UiO type MOFs comprises the following steps: ①. Add metal salt, organic ligand and regulator into DMF and dissolve evenly to form a precursor solution; ②, put the precursor solution prepared in step ① into a reactor lined with polytetrafluoroethylene, put it in an oven and heat it for 12-24 h, cool it to room temperature and centrifuge it, wash the precipitate with ethanol and deionized water, and dry it to obtain UiO type MOFs; In step ①, the metal salt is any one of zirconium chloride and zirconium oxychloride, the organic ligand is any one of terephthalic acid, biphenyl-4-4'-dicarboxylic acid and trimesic acid, and the regulator is any one of formic acid, acetic acid and benzoic acid.

2. A high-strength polytetrafluoroethylene cable film according to claim 1, characterized in that: The method for preparing the aluminum oxide nanofibers comprises the following steps: A1. Dissolve aluminum salt in water, add aluminum powder, mix well, and react at 60-80℃ for 6-12 hours to obtain aluminum sol solution; A2, adding polyvinyl alcohol and polyvinyl pyrrolidone to the aluminum sol solution prepared in step A1, stirring evenly until the solution becomes a transparent and viscous mixture, injecting it into the syringe of the electrospinning device, starting the electrospinning device, stretching the mixture into nanofibers through the action of the electrostatic field, collecting it on a collecting plate, and forming a fiber film; A3. Dry the fiber membrane obtained in step A2, sinter it at 600-800°C for 2-4 h, and then cool it to room temperature to obtain alumina nanofibers.

3. A high-strength polytetrafluoroethylene cable film according to claim 2, characterized in that: In step A1, the aluminum salt is any one of aluminum chloride and aluminum nitrate, and the mass ratio of the aluminum salt to water is 20-30:100; the mass ratio of the aluminum powder to the aluminum salt is 1:

1.

4. A high-strength polytetrafluoroethylene cable film according to claim 3, characterized in that: In the step A2, the mass ratio of polyvinyl alcohol to polyvinyl pyrrolidone is 1:1, and the mass ratio of polyvinyl alcohol to aluminum salt is 1:

1.

5. A high-strength polytetrafluoroethylene cable film according to claim 4, characterized in that: The silane coupling agent comprises the following raw materials in parts by weight: 1-2 parts of 3-aminopropyltriethoxysilane, 4-6 parts of γ-aminopropyltrimethoxysilane, and 3-5 parts of 3-methacryloxypropyltrimethoxysilane.

6. A high-strength polytetrafluoroethylene cable film according to claim 5, characterized in that: The antioxidant is 2,6-di-tert-butyl-4-methylphenol.

7. A method for preparing a high-strength polytetrafluoroethylene cable film according to any one of claims 1 to 6, characterized in that: The specific steps include: S1. Mix polytetrafluoroethylene, alumina nanofibers, UiO-type MOFs, silane coupling agent, antioxidant, triphenyl phosphate and deionized water uniformly according to weight parts to obtain a mixed solution; S2, placing the mixed solution prepared in step S1 into a mold, and preparing a formed film by hot pressing; S3, performing surface grinding processing on the film formed in step S2 to obtain a high-strength polytetrafluoroethylene cable film.